2016
DOI: 10.1111/jphp.12458
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of spray-dried co-amorphous drug–amino acid salts

Abstract: It could be shown that strong intermolecular interactions between drug and co-amorphous coformer that persist during the dissolution are crucial to prevent recrystallization and to enhance dissolution of a co-amorphous formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 32 publications
7
72
0
Order By: Relevance
“…Amorphous salt formation has previously been observed between Ind and Arg (14,19). Fur-Arg mixtures are expected to interact in a similar way, including the Fur carboxylic acid group and the Arg guanidine group as salt formers.…”
Section: Co-amorphous Drug-amino Acid Mixtures Including Salt Formationmentioning
confidence: 90%
See 1 more Smart Citation
“…Amorphous salt formation has previously been observed between Ind and Arg (14,19). Fur-Arg mixtures are expected to interact in a similar way, including the Fur carboxylic acid group and the Arg guanidine group as salt formers.…”
Section: Co-amorphous Drug-amino Acid Mixtures Including Salt Formationmentioning
confidence: 90%
“…One advantage of ball milling is that it is inflicting only very limited chemical degradation (17), specifically for some indomethacin systems degradation levels of less than 1.5% were found (13). Recently, spray-drying has been demonstrated to be another suitable production method for the preparation of co-amorphous systems (18,19). Co-amorphous formulations, in which a given drug is stabilized by another drug molecule, were introduced in order to reduce the amount of excipient needed and eventually to allow the simultaneous administration of several drugs in a single dosage form.…”
Section: Introductionmentioning
confidence: 98%
“…The significant effect of ARG could be expected from three sources; 1) the results of dissolution tests with crystalline material, 2) the major intrinsic dissolution rate increases described in the studies of Löbmann et al and Jensen et al, and 3) the supersaturation already observed by Lenz et al [24,40,43]. The highest supersaturation maintained by ARG in FaSSIF blank and FaSSIF was probably due to the higher pH, which led to the ionization of IND, promoting electrostatic interactions with ARG [32].…”
Section: Discussionmentioning
confidence: 99%
“…Coformers that have been successfully applied to stabilize an amorphous drug include saccharin (Gao et al, 2013), nicotinamide (Shayanfar, 2013), carboxylic acids (Lu and Zografi, 1998;Masuda et al, 2012;Hoppu et al, 2007Hoppu et al, & 2009Ali et al, 2015;Han et al, 2016;Hu et al, 2014) and sugars (Descamps et al, 2007). In particular, amino acids capable of forming charge-assisted hydrogen bonds have been widely studied (Löbmann et al, 2013;Jensen et al, 2014Jensen et al, , 2015Jensen et al, & 2016Laitinen et al, 2014;Lenz et al, 2015;Huang et al, 2016;Craye et al, 2015). On the other hand, an increase in the physical stability was observed for coamorphous simvastatin-glipizide, even though there was no evidence for intermolecular interactions, suggesting that molecular level mixing may be sufficient to stabilize the amorphous phase (Löbmann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%